1994
DOI: 10.1111/j.1095-8312.1994.tb00944.x
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of contaminants in sediments of the Inner Bristol Channel and Severn Estuary

Abstract: In the inner Bristol Channel and Severn Estuary, most contaminated stations were in muddy, depositional areas of the estuary, particularly along the Welsh coast between the Rivers Taff and Usk, and also on the English coast between Avonmouth and Severn Beach. Some deeper areas, dominated by sand and mixed sediments, also showed contaminant concentrations in excess of those predicted from sediment texture, organic matter, and aluminium or iron concentrations.Concentrations of lead, copper, chromium, nickel and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Potter et al (2001) documented an increase between the 1970s and 1990s in the annual fish catches from the intake screens of the Oldbury Power Station in the Severn Estuary. These authors suggested that the marked increases in abundance of species such as sand goby Pomatoschistus minutus (Pallas), whiting Merlangius merlangus (L.), bass Dicentrarchus labrax (L.), thin-lipped grey mullet Liza ramada (Risso), herring, sprat and Norway pout Trisopterus esmarkii (Nilsson) reflects the great improvement that occurred in the water quality of the Severn Estuary between these decades (Little & Smith, 1994).…”
Section: Thames Estuarymentioning
confidence: 99%
“…Potter et al (2001) documented an increase between the 1970s and 1990s in the annual fish catches from the intake screens of the Oldbury Power Station in the Severn Estuary. These authors suggested that the marked increases in abundance of species such as sand goby Pomatoschistus minutus (Pallas), whiting Merlangius merlangus (L.), bass Dicentrarchus labrax (L.), thin-lipped grey mullet Liza ramada (Risso), herring, sprat and Norway pout Trisopterus esmarkii (Nilsson) reflects the great improvement that occurred in the water quality of the Severn Estuary between these decades (Little & Smith, 1994).…”
Section: Thames Estuarymentioning
confidence: 99%